Child and Human Development in perspective - Tau, Ramiro (2023)
The notion of “human development” is used polysemically in everyday language, it is present in popular media, political discourse, and several different branches of the sciences, and these iterations often contain ambiguities that are the result of non-specific notion of “development”. In very broad terms, “development” usually refers to the progressive series of changes in a behavior, a function or a structure throughout the life of a person, an organism or a society. Within this series of changes, “the possible” is often characterized as the constantly evolving spectrum of future scenarios, usually in the form of an unachieved but prefigured stage or phase, or as the opening toward essentially unpredictable transformations. In any case, it is possible to recognize in this diversity a series of common, although generally diffuse, ideas: change over time, evolution, growth, transformation, increase of certain magnitudes, and the passage from a potential and latent state to a current and expressed one. When the notion of development refers explicitly to the human, it can suggest changes in phenomena as wide-ranging as those concerning the biological body, and the mind of the individual to the political and economic macro-processes that take place in large societies. However, the notion of “human development” is most often used as a syncretic category, bringing together in a holistic way all these biological, psychological, or social dimensions. In these cases, it is often confused with some form of evolution, both in its teleological versions or in those that do not recognize a pre-designed directionality, even if they attempt to explain or describe changes over time. These different conceptions of human development are always supported by a corpus of metatheoretical assumptions. In particular, those commitments that refer to the recognized entities, the nature of changes, and the reasons for their occurrence.